2015
DOI: 10.5951/jresematheduc.46.1.0039
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Children's Algebraic Thinking: The Impact of a Comprehensive Early Algebra Intervention in Third Grade

Abstract: This article reports results from a study investigating the impact of a sustained, comprehensive early algebra intervention in third grade. Participants included 106 students; 39 received the early algebra intervention, and 67 received their district's regularly planned mathematics instruction. We share and discuss students' responses to a written pre- and post-assessment that addressed their understanding of several big ideas in the area of early algebra, including mathematical equivalence and equations, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
148
2
32

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(218 citation statements)
references
References 11 publications
15
148
2
32
Order By: Relevance
“…In our current work -Project LEAP (http:// algebra.wceruw.org) -we are addressing the aforementioned question and specifically whether children who experience comprehensive and sustained early algebra in grades 3-5 are better prepared for algebra in secondary school than children who have a traditional arithmetic-based experience in grades 3-5. To date, our findings indicate that elementary school children are capable of learning foundational algebraic concepts and skills and that a comprehensive and sustained early algebra experience significantly affects their algebra understanding (Blanton et al, 2015). For example, students in the early algebra classrooms demonstrated the ability to:…”
Section: #3 Student Success In Algebra Also Requires An Ability To Dmentioning
confidence: 88%
“…In our current work -Project LEAP (http:// algebra.wceruw.org) -we are addressing the aforementioned question and specifically whether children who experience comprehensive and sustained early algebra in grades 3-5 are better prepared for algebra in secondary school than children who have a traditional arithmetic-based experience in grades 3-5. To date, our findings indicate that elementary school children are capable of learning foundational algebraic concepts and skills and that a comprehensive and sustained early algebra experience significantly affects their algebra understanding (Blanton et al, 2015). For example, students in the early algebra classrooms demonstrated the ability to:…”
Section: #3 Student Success In Algebra Also Requires An Ability To Dmentioning
confidence: 88%
“…Recent research challenges so-called limitations in children's capacities to work with algebraic topics (Brizuela & Martinez, 2012;Cai & Knuth, 2011;Molina & Ambrose, 2008). As summarized elsewhere (e.g., Blanton, Stephens, Knuth, Gardiner, Isler, & Kim, 2015), these capacities concern children's ability to develop relational thinking; use different representations to express generalizations; represent verbal statements as algebraic equations; and reason about and represent relationships between abstract quantities of physical measures.…”
Section: Introductionmentioning
confidence: 99%
“…The national elementary mathematics curriculum in Korea does not emphasize directly essential elements of algebraic thinking but indicates indirectly some of them. This study compared our students' performance related to algebraic thinking with results of Blanton et al (2015) which reported considerable progress of algebraic thinking by emphasizing it through a regular curriculum. The results of this study showed that Korean students solved many items correctly as compatible to Blanton et al (2015).…”
mentioning
confidence: 99%
“…This study compared our students' performance related to algebraic thinking with results of Blanton et al (2015) which reported considerable progress of algebraic thinking by emphasizing it through a regular curriculum. The results of this study showed that Korean students solved many items correctly as compatible to Blanton et al (2015). However, our students tended to use 'computational' strategies rather than 'structural' ones in the process of solving items related to equation.…”
mentioning
confidence: 99%